Not in the Hardware Aisle, Please: Same-Sex Marriage, Anti-Gay Activism and My Fabulous Gay Wedding - Pearson, Wendy (Ethnologies, 2006)
My Fabulous Gay Wedding was intended from its conception to be “a hot topic, a controversial topic, a topic filled with lots of opportunity for emotional moments.” This article traces a number of contemporary discourses around same-sex marriage that are illuminated, albeit not clarified, by responses to the show, including a boycott of Canadian Tire, a purported sponsor, by a number of right-wing, anti-gay groups. However, the questions the show raises exceed the media’s simplistic binary of “lesbian and gay rights” v. “religious rights” and involve interrogating what, exactly, is being represented on screen, and whether or not same-sex weddings interpellate lesbian and gay couples into a form of heteronormativity.